2006
DOI: 10.2174/138161206778194088
|View full text |Cite
|
Sign up to set email alerts
|

Drug Hypersensitivity: Epidemiology and Risk Factors

Abstract: Drug allergies are heterogeneous and multifactorial diseases and are always the consequence of an exaggerated immune-mediated reaction. Previously described models of immunologic mechanisms (mainly based on Gell and Combs' classification) cannot fully explain the physiopathology of these diseases; it seems therefore important to identify risk factors. Clinical and biologic tests are helpful diagnostic tools but are limited in their sensitivity and reliability and are certainly not predictive. Epidemiologic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
16
1
1
Order By: Relevance
“…The drug hypersensitivity reactions in patients might be manifested by many cofactors, such as individual medical history, coadministered drugs, underlying diseases, viral infections, regulatory T-cell population/function, genetic polymorphisms of metabolic enzymes/immune-related genes, or autoimmune disorders. 39,40 Therefore the results presented in this study could not be extrapolated simply to the clinical situations of patients.…”
Section: Discussionmentioning
confidence: 96%
“…The drug hypersensitivity reactions in patients might be manifested by many cofactors, such as individual medical history, coadministered drugs, underlying diseases, viral infections, regulatory T-cell population/function, genetic polymorphisms of metabolic enzymes/immune-related genes, or autoimmune disorders. 39,40 Therefore the results presented in this study could not be extrapolated simply to the clinical situations of patients.…”
Section: Discussionmentioning
confidence: 96%
“…For example, subjects with a prior medical history of viral infection (eg, HIV and human herpesvirus) or autoimmune disorders (eg, systemic lupus erythematosus) have been noted to be more susceptible to drug hypersensitivity. 33,34 Because OXC is the prodrug of CBZ and they share structural similarity, the cross-reactivity between CBZ and OXC to T cells has been examined in patients, and it has been reported that 33% of the patients who had a CBZ-induced rash also had OXC hypersensitivity. 35 T cells isolated from patients with CBZ hypersensitivity showed cross-reactivity to OXC in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are women, HIV and herpes-infected patients, and systemic patients with lupus erythematosus (SLE). 2 As a general principle, patients with SLE seem to have higher frequencies of hypersensitivity reactions to antibiotics than healthy populations. 3 In this study, we compared the frequency of drug allergies between 2 autoimmune diseases from the same urban population.…”
mentioning
confidence: 99%